The Relationship of Emotional Intelligence to the ‎Collective Efficacy Beliefs among Mathematics Teachers in ‎the Sultanate of Oman - Al Shuaibi, Moza; Aldhafri, Said (Jordan Journal of Educational Sciences, 2020)
The study aimed at identifing the relationship between emotional intelligence and collective efficacy beliefs of mathematics teachers in Oman. The sample of the study was randomly stratified one, that consisted of (1226) teachers from all governorates of the Sultanate of Oman. The study used two measures: The emotional intelligence scale (Schutte et al., 1998) and the scale of the collective efficacy beliefs (Aldhafri, 2006). The results of the study showed that there are high levels of teachers’ emotional intelligence and collective efficiency beliefs. Female teachers scored higher than males in the dimensions of emotional intelligence, as well as in collective efficacy beliefs. The results also indicated that some dimensions of emotional intelligence (understanding and expression of self-feelings and self-feelings regulation) are positively predicted by collective efficacy beliefs.